Deletion of CD36 exhibits limited impact on normal hematopoiesis and the leukemia microenvironment - Yiting Meng; Mateusz Pospiech; Atham Ali; Ritu Chandwani; Mary Vergel; Sandra Onyemaechi; George Yaghmour; Rong Lu; Houda Alachkar (Cellular & Molecular Biology Letters, 2023)
Abstract Background CD36 has been identified as a potential therapeutic target both in leukemic cells and in the tumor immune microenvironment. In acute myeloid leukemia (AML), we found that APOC2 acts with CD36 to promote leukemia growth by activating the LYN-ERK signaling. CD36 also plays a role in lipid metabolism of cancer associated T-cells leading to impaired cytotoxic CD8+ T-cell and enhanced Treg cell function. To establish CD36 as a viable therapeutic target in AML, we investigated whether targeting CD36 has any detrimental impact on normal hematopoietic cells. Methods Differential expression data of CD36 during human and mouse normal hematopoiesis were examined and compared. Cd36 knockout (Cd36-KO) mice were evaluated for blood analysis, hematopoietic stem cells and progenitors (HSPCs) function and phenotype analyses, and T cells in vitro expansion and phenotypes in comparison with wild type (WT) mice. In addition, MLL-PTD/FLT3-ITD leukemic cells were engrafted into Cd36-KO and WT mice, and leukemia burden was compared between groups. Results RNA-Seq data showed that Cd36 expression was low in HSPCs and increased as cells matured. Phenotypic analysis revealed limited changes in blood count except for a slight yet significantly lower red blood cell count and hemoglobin and hematocrit levels in Cd36-KO mice compared with WT mice (P < 0.05). In vitro cell proliferation assays of splenocytes and HSPCs from Cd36-KO mice showed a similar pattern of expansion to that of cells from WT mice. Characterization of HSPCs showed similar percentages of the different progenitor cell populations between Cd36-KO with WT mice. However, Cd36-KO mice exhibited ~ 40% reduction of the number of colonies developed from HSPCs cells compared with WT mice (P < 0.001). Cd36-KO and WT mice presented comparably healthy BM transplant in non-competitive models and developed similar leukemia burden. Conclusions Although the loss of Cd36 affects the hematopoietic stem cell and erythropoiesis, limited detrimental overall impact was observed on normal Hematopoietic and leukemic microenvironments. Altogether, considering the limited impact on normal hematopoiesis, therapeutic approaches to target CD36 in cancer are unlikely to result in toxicity to normal blood cells.